Scenarios For Freight Railway Transport Development Within Intermodal Network in Poland Until 2020 - Marzena KRAMARZ; Edyta PRZYBYLSKA (Communications of International Proceedings, 2021)
Current transport policy draws attention to the intermodal transport development wherein the railway transport is the main link. Therefore, the paper discloses a developed methodology of application of the scenario-based analysis during evaluation of the directions of the railway freight transport development within the intermodal transport network (ITN). The prepared methodology was used in the Polish railway transport considering 10-year long timeline. The adopted approach was developed by the authors by determining the importance of individual factors affecting the railway transport development within ITN. This importance was used to determine the weighted impact force of the factors within three types of scenarios under development.
Keywords: Intermodal Transport Network (ITN); Scenario Analysis; Key Factors; Weighted Impact Force